Mixing secrets for the small studio - Senior, Mike (Focal Press, 2011)
In the book, Mike shares his own numerous tips, as well as tricks heÕs learnt from some of the industryÕs top engineers, including Michael Brauer, Chris and Tom Lord-Alge, Tony Maserati, Andy Wallace and many more. At well over 300 pages, thereÕs plenty of information to digest, and itÕs all been helpfully categorised and split into easily navigable chapters. The book covers topics such as monitoring, including speaker types and room acoustics; mix preparation, from fixing timing and tuning errors to modifying a songÕs arrangement; effects and processing, including the use of reverb, delay, EQ and compression; and finishing a mix, as well as dealing with revision requests made by the client. At the end of each chapter is a section titled Cut To The Chase, which summarises all the points made therein.\As well as providing all this information, Mike has produced over 350 audio files to accompany the chapters in the book, provided in both MP3 and uncompressed WAV formats. HeÕs also sought out bands and producers kind enough to agree to make unmixed multitracks of their recordings available for budding mix engineers to practice mixing with. These are available to everyone, for free, at http://cambridge-mt.com/ms-ch15.htm#audio.\A copy of the book has been doing the rounds at SOS HQ, and everyone whoÕs seen it has been very impressed by the quality and range of information. Available now, Mixing Secrets For The Small Studio can be bought for around £20. For more information, check out the web site below.